Circulating current minimisation of paralleled 400 Hz three‐phase four‐leg inverter based on third harmonics injection. Issue 13 (12th April 2018) - Chen, Yihan; Guo, Honghao; Ma, HaiXiao; Zhou, Yan
Abstract : In this study, according to zero‐sequence current modelling of fourth leg, the control strategy for suppressing circulating current is proposed. Meanwhile, a control method based on average current loops and third harmonic injection loop has been applied in the parallel 3p4l inverter system, consequently, the peak value of circulating current is improved by third harmonic signals. In order to suppress circulating current and minimise the number of interconnecting wires between inverters, output impedance modelling is established, and feed‐forward loop of zero‐sequence circulating current is added upon current loop accordingly. The proposed control method could be implemented by using analogue design and related to 400 Hz paralleled inverter systems. Both simulation and experimental results indeed show the effectiveness of the proposed control.